Shopping in the Metaverse: An Exploratory Study of Fashion Shops - Torres-Martín, José-Luis; Pérez-Ordóñez, Cristina; Castro, Andrea; Villena-Alarcón, Eduardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The metaverse has revolutionized the fashion industry by enabling fashion brands to engage with consumers through immersive virtual stores. These virtual environments offer innovative and interactive experiences, allowing textile companies to connect with their audiences in new ways. This study conducts an exploratory analysis to examine how storytelling is implemented in virtual fashion stores in the metaverse, focusing on the case study of Tommy Hilfiger in Roblox and Decentraland. The findings emphasize the importance of personalization and interaction in shaping the brand experience.